Review of long-term economic projections for selected countries in the ECAFE region : report.of the Forth Group of Experts on Pragramming Techniques ? - United Nations (Bangkok : United Nations, Economic Commission for Asia and the Far East, 1964)
The present report was prepared by a group of ten experts, all from within the region. The report represents the unanimous views of the experts who acted in their personal capacities; accordingly, these views should not be identified with any of the organizations with which they are associated
United Nations. [Document] E/CN.11/674.
"United Nations publication. Sales no.: 65.II.F.6."
osc 12/12/2018
Loans
Keywords: Economic development; Economic history; Economic forecasting; Asia; East Asia